Análise mecânica da argamassa para revestimento com a incorporação do detergente - Medeiros, Wanderson Emanoel Morais de (Universidade Federal Rural do Semi-Árido, 2019)
As the mortars must be prepared to absorb small deformations in a way that guarantees the stability of the masonry, that is, it performs well and presents good durability. When the quality of the mortar is compromised, cracks can occur, which is one of the most worrisome pathological manifestations in mortar coatings. With the growth of civil construction in the last years, the development of several construction techniques and the increase of the materials inputs in the works. Without the initial study and without a product potentiating language, it is one of the earliest future disorders such as mortars produced. Believing the possibility of the detergent being used as a cleaning agent of the mortar, this work analyzed the behavior of the fresh and hardened state of the mortar with addition of detergent. The tests were performed after 28 days of cure in a mortar with 1: 3 trace (cement: sand), always looked for one without addition of detergent with traces of mortar with the additions of 5g, 10g and 15g of detergent with respect to the mass of the cement. Through the analysis of consistency it has not applied the increase of the workability to measurement which includes the additive content of detergent. This study was to use assay, the detergent had a function of delaying the initial handle of the mortar. However, the tensile tests in flexion and compression increased with increasing amount of detergent added to the mortar. Therefore, the detergent like additive is the mortar can slow down once and for all, over time, the ability to reduce its capacity, functioning as a treatment of future problems.
Monografia
Keywords: Aditivos; Detergente; Deformação em argamassa; Additives; Detergents; Mortar deformation; ENGENHARIAS::ENGENHARIA CIVIL